PELIBATAN ORANG TUA BERNUANSA KEARIFAN LOKAL DALAM PEMBELAJARAN ANAK USIA DINI - -, WAHYUNIATI; ABDILLAH, HUSNI (Jurnal Pendidikan Usia Dini, 2017)
This study aims to: Analyzing the form of parent participation in school learning activities that have a value of local knowledge, Subjek research include school principals, teachers and parents from TK Falasifa, TK Baiturrahman and RA jannatul Abror. This research use descriptive qualitative method, Data collection techniques such as interviews and in-depth observation. While analysis of the data used include: coding step, reduction, display and conclusion. The results of the research, that: The activities developed nuanced local wisdom to develop parent involvement consists of: Tahlil and istighosah routine on Friday earlier month involving parents, Rated affection by sharing with the orphans of tuition. Values of mutual cooperation and â€œngalapberkahâ€, Visits to the Old Orphanage Together, value mutual cooperation, the value Sepiingpamrihrameinggawe, and tepaselira value.Paguyupan value, and the perception of a teacher is considered as a highly mbarokahi, Ikhlas kiaine ilmunevalue, patuhgurunebarokahuripe value. Guardians of students willing to contribute and work together. Keywords: Teacher, involvement of parents, local wisdom